Economic integration and multinational investment behavior : European and East Asian experiences - Ruffini, Pierre-Bruno (Cheltenham, UK ; Northampton, MA: Edward Elgar, 2004)
This book presents important and original studies of international trade and investment in relation to regional economic integration, with particular reference to the experiences of Europe and East Asia. The distinguished contributors illustrate and explain how the location decisions of firms, international trade and capital flows can form, stimulate and shape economic regions in the global economy.
"Chapters in this volume were originally presented ... at the international conference 'Location of economic activity, regional development and the global economy--European and East Asian experiences' held at ... the University of Le Havre (France) on 26-27 September 2001"--Preface.
Includes bibliographical references and index.
lje 4/8/2016
Loan
Keywords: International economic cooperation; Investments, Foreign; Investments, Foreign; Europe; East Asia